Perineal Protrusion Secondary to Imperforate Hymen and Hydrocolpos in an 8-Year-Old Spayed Female Dog - Callie L. Blackford Winders; Karen M. Tobias (Case Reports in Veterinary Medicine)
An 8-year-old female spayed Dachshund presented with an acute onset of dysuria, dyschezia, and painful perineal protrusion. A perineal hernia was ruled out on digital rectal examination, and blood work was unremarkable. An extremely dilated vagina was identified on computed tomography, and hydrocolpos was suspected. Endoscopic vaginal exam confirmed the diagnosis of imperforate hymen. The membrane was ruptured digitally and remnants were removed endoscopically, resulting in resolution of clinical signs. Imperforate hymen is a rare congenital abnormality that can result in extensive fluid accumulation within the vagina and subsequent compression of local structures or secondary infection. Treatment of hydrocolpos includes membrane perforation and removal.